2000
DOI: 10.4319/lo.2000.45.8.1818
|View full text |Cite
|
Sign up to set email alerts
|

Domoic acid production near California coastal upwelling zones, June 1998

Abstract: Sea lion mortalities in central California during May and June 1998 were traced to their ingestion of sardines and anchovies that had accumulated the neurotoxin domoic acid. The detection of toxin in urine, feces, and stomach contents of several sea lions represents the first proven occurrence of domoic acid transfer through the food chain to a marine mammal. The pennate diatoms, Pseudo-nitzschia multiseries and P. australis, were the dominant, toxinproducing phytoplankton constituting algal blooms near Monter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
150
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(162 citation statements)
references
References 36 publications
11
150
1
Order By: Relevance
“…It is possible that the M'diq bay area experienced an increase in nutrients during these periods. Several studies suggested that Pseudo-nitzschia blooms are associated with cool and high nutrient waters (TRAINER et al 2000). Pseudo-nitzschia abundance has a positive correlation with water temperature, phosphate and ammonium (LJUBE [I] et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the M'diq bay area experienced an increase in nutrients during these periods. Several studies suggested that Pseudo-nitzschia blooms are associated with cool and high nutrient waters (TRAINER et al 2000). Pseudo-nitzschia abundance has a positive correlation with water temperature, phosphate and ammonium (LJUBE [I] et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both sources stimulate Pseudo-nitzschia blooms at concentrations of 8-22 mM NO 3 À , 2.4-35 mM Si and 0.2-2 mM PO 4 3À (Dortch et al, 1997;Scholin et al, 2000;Trainer et al, 2000;Loureiro et al, 2005), but in different temperature and salinity regimes. Pseudo-nitzschia abundances and DA concentrations on the west coast of the U.S. are associated with low temperature, high salinity and high nutrient conditions typical of upwelling (Villac, 1996;Trainer et al, 2000Trainer et al, , 2002. Similarly, upwelling regions off the coast of Portugal contain high numbers of Pseudonitzschia cells, which are used as upwelling indicators during spring and summer (Moita, 2001;Loureiro et al, 2005).…”
Section: Ecological Profile Of Pseudo-nitzschia Speciesmentioning
confidence: 98%
“…Harmful algal bloom (HAB) species include representatives from a number of planktonic taxa that are associated with negative impacts for wildlife (e.g., Trainer et al 2000;Scholin et al 2000;Landsberg 2002), human health, and local economies (e.g., Prakash et al 1971;Steidinger and Baden 1984;Kirkpatrick et al 2004). While considerable progress has been made toward understanding the bloom dynamics of HAB species through ship-based surveys, much of that work has entailed substantial post-sampling laboratory analyses that are time and labor-intensive.…”
Section: Introductionmentioning
confidence: 99%